1993
DOI: 10.1254/jjp.63.369
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Centrally Acting Muscle Relaxants on the Intrathecal Noradrenaline-Induced Facilitation of the Flexor Reflex Mediated by Group II Afferent Fibers in Rats

Abstract: ABSTRACT-The effects of centrally acting muscle relaxants on the flexor reflex mediated by group II afferent fibers (group II flexor reflex) in anesthetized intact rats and on the intrathecal noradrenaline-HC1 induced facilitation of the group II flexor reflex in anesthetized spinal rats were investigated. In anesthetized intact rats, mephenesin, tolperisone-HCI, chlorpromazine-HC1 and baclofen inhibited the group II flexor reflex dose-dependently, whereas the inhibitory effect of tizanidine-HC1 was bell-shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Elenine and chlorpromazine, 30 min after administration, produced an almost total inhibition of traction performance when a dose of 10, 20, and 40 mg/kg was given. This effect is well known for chlorpromazine [25, 26] and has also been observed with lignans from Justicia pectoralis [21]. These results are in accordance with those obtained by Kuribara et al [27], so that the test can be used to distinguish between a primary muscular relaxant (diazepam) a primary neuroleptic (chlorpromazine) and a more general central depressant (pentobarbital) activity.…”
Section: Discussionsupporting
confidence: 88%
“…Elenine and chlorpromazine, 30 min after administration, produced an almost total inhibition of traction performance when a dose of 10, 20, and 40 mg/kg was given. This effect is well known for chlorpromazine [25, 26] and has also been observed with lignans from Justicia pectoralis [21]. These results are in accordance with those obtained by Kuribara et al [27], so that the test can be used to distinguish between a primary muscular relaxant (diazepam) a primary neuroleptic (chlorpromazine) and a more general central depressant (pentobarbital) activity.…”
Section: Discussionsupporting
confidence: 88%
“…Each of these compounds was evaluated a third time in the locomotion assay at a concentration of 100 µM, and subsequently monitored for forebrain electrographic activity. Clorgiline (a monoamine oxidase A inhibitor) and the muscle relaxants zoxazolamine 37 and tolperisone 38 were identified as “false positives” because they reduced swim activity at this concentration but when the same mutant was embedded in agar electrographic seizure events were still observed (see Fig. 6E).…”
Section: Resultsmentioning
confidence: 99%
“…showed qualitatively and quantitatively similar effects. It was concluded that tolperisone, as a centrally acting muscle relaxant depresses group II flexor reflex by inhibiting descending noradrenergic tonic facilitation within the spinal cord [20]. …”
Section: Pharmacological Data Of Tolperisone On Whole Animalsmentioning
confidence: 99%